2018
DOI: 10.1159/000493485
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative RT-PCR Assay for Detecting Lymph Node Metastasis in Endometrial Cancer: A Preliminary Study

Abstract: Objective: The detection accuracy of sentinel lymph node (SLN) metastasis by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) for endometrial cancer (EC) remains unclear and was assessed in this preliminary study. Methods: We studied primary cancer tissues and pelvic lymph nodes (PLN) from 105 patients with EC. qRT-PCR assay was performed to determine the copy numbers of CK19 mRNA in EC tissues, and negative and positive LN samples. Further, qRT-PCR results were compared with pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There are manuscripts describing advanced molecular techniques (for example qRT-PCR) in detecting EC lymph node micrometastases [94][95]. These techniques are even more sensitive than IHC, but they also carry high false-positive results [94][95].…”
Section: Cytokeratins and Ec Micrometastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are manuscripts describing advanced molecular techniques (for example qRT-PCR) in detecting EC lymph node micrometastases [94][95]. These techniques are even more sensitive than IHC, but they also carry high false-positive results [94][95].…”
Section: Cytokeratins and Ec Micrometastasesmentioning
confidence: 99%
“…There are manuscripts describing advanced molecular techniques (for example qRT-PCR) in detecting EC lymph node micrometastases [94][95]. These techniques are even more sensitive than IHC, but they also carry high false-positive results [94][95]. Interestingly, Pappa et al [94] assumed that "..qRT-PCR exhibits a better diagnostic accuracy compared with IHC (for the detection of lymph node micrometastasis in cervical, endometrial and vulvar cancer), while CK19 displays a consistent pattern of detection compared to carbonic anhydrase 9…".…”
Section: Cytokeratins and Ec Micrometastasesmentioning
confidence: 99%
“…Numerous candidate genes (over 24 genes for endometrial carcinoma) with specific expression in carcinomas and no expression in lymphatic or soft tissues (17) revealed cytokeratin 19 (CK19) m-RNA as the best target to use for metastatic carcinoma cells. Togami et al (18) used qRT-PCR to detect and quantify CK19 mRNA in endometrial carcinomas and found 104/106 (98%) positive cases. In this study qRT-PCR of 12 pelvic lymph node (PLN) metastases reached best sensitivity and specificity without discrepancies between pathology report and molecular test when "positivity" of PLNs was determined above 4,500 copies/µL.…”
mentioning
confidence: 99%